Handbook of Software Engineering Methods - Letaw, Lara (Open textbook library., 2024)
Software engineering can help people create sustainable, extensible programs that solve problems people care about.I won’t tell you how to be a software engineer; you’ll learn that over time by doing it. Instead, this book is about software engineering methods: Ways people achieve specific objectives in software engineering—that can save your project. My hope is that, after reading this book (or parts of it), you’ll feel better equipped for software engineering.